OPPORTUNITIES OF ARTIFICIAL INTELLIGENCE AND INTEGRATION IN MODERNIZING THE ENVIRONMENTAL EDUCATION SYSTEM FOR STUDENTS - Gulnoza Istamovna Egamova (Bright Mind Publishing, 2025)
This article examines the possibilities of modernizing the ecological education system for students through the use of artificial intelligence and an integrative approach. In the context of digital transformation, the formation of ecological awareness and culture in harmony with sustainable development goals is a pressing issue. The study highlights the application of artificial intelligence tools (chatbots, adaptive learning platforms, analytical systems) and integrative pedagogical technologies in ecological education. Results of an experiment involving students aimed at improving the effectiveness of ecological education are presented. Based on the findings, scientific and practical recommendations for enhancing ecological education using modern technologies are formulated.
Keywords: Ecological education, students, artificial intelligence, integrative approach, modern technologies, ecological awareness, sustainable development, digital learning, AI technologies, innovative pedagogy.